Modulation of bone metabolism and mineralization in gilthead seabream (Sparus aurata) fed various vegetable oil sources - Barrios Guzmán, Carmen Lucía (2015)
Little information exists on the role of dietary lipids on the bone metabolism in fish. A trial was undertaken to evaluate the effect of dietary lipid sources as modulators of bone fatty acid composition, mineralization and skeletal metabolism in fast-growing seabream juveniles. Twelve homogenous groups of 25 seabream juveniles each (mean initial body weight of 39.3  1.4 g) were stocked in 90 L tanks and fed one of four semi-purified experimental diets formulated to be isonitrogenous (crude protein, 46% DM), isolipidic (15% DM) and isoenergetic, but with variable oils sources. The dietary lipid sources under testing were: a) cod liver oil (FO, a source of n-3 LC-PUFA); b) soybean oil (SBO, a source of n-6 fatty acids); c) linseed oil (LSO, a source of non-LC-PUFA n-3 fatty acids); and d) palm oil (PO, a source of saturated fatty acids). Overall growth performance criteria and whole-body composition of fish were not significantly affected by the various dietary experimental treatments (P>0.05). Bone fatty acid composition was altered by the dietary fatty acid profile, but suggests the existence of conservative mechanisms for some specific fatty acids, namely DHA. While the calcium content of bone was little affected by the dietary treatments, bone phosphorus level in seabream fed the cod liver oil diet was significantly higher (P<0.05) than those found in fish fed the vegetable oil diets. Microscopic observation of tetracycline-marked vertebrae showed that mineral deposition in vertebrae of fish fed the LSO diet was significantly lower (P<0.05) than that found in fish fed the FO and SBO diets. Tartrate-resistant acid phosphatase (TRAP) activity in bone homogenate was positively correlated (r = 0.658) with α-linolenic acid (ALA, 18:3n-3) intake, while an increased intake of EPA (r = -0.478) and DHA (r = -0.536) tended to reduce TRAP activity. Alkaline phosphatase (ALP) activity in bone homogenates was positively correlated with intake of EPA (r = 0.763) and DHA (r = 0.793). In comparison to fish fed the FO and LSO diets, those fed the SBO and PO diets showed a significant reduction (P<0.05) of total phospholipase A2 (PLA2) activity in bone homogenates. However, such changes could not be clearly attributable to cytosolic PLA2. Overall data confirm that dietary lipids are important modulators of bone metabolism in a marine teleost, such as gilthead seabream.